(untitled) (American Journal of Business Management, Economics and Banking, 2026)
Modern technologies and artificial intelligence (AI) play a decisive role in economic development, transforming key industries and increasing the efficiency of production and management processes. This article analyzes the impact of AI on the global threat, the key main areas of its application, and also considers the challenges and forecasts associated with its implementation. The study is based on a literature review, as well as an analysis of data on the impact of AI on economic development in various countries and industries.